Empirical evidence on the relation between stock option compensation and risk taking - Rajgopal, Shivaram; Shevlin, Terry (Journal of Accounting and Economics, 2002)
We examine whether executive stock options (ESOs) provide managers with incentives to invest in risky projects. For a sample of oil and gas producers, we examine whether the coefficient of variation of future cash flows from exploration activity (our proxy for exploration risk) increases with the sensitivity of the value of the CEO's options to stock return volatility (ESO risk incentives). Both ESO risk incentives and exploration risk are treated as endogenous variables by adopting a simultaneous equations approach. We find evidence that ESO risk incentives has a positive relation with future exploration risk taking. Additional tests indicate that ESO risk incentives exhibits a negative relation with oil price hedging in a system of equations where ESO risk incentives and hedging are allowed to be endogenously determined. Overall, our results are consistent with ESOs providing managers with incentives to mitigate risk-related incentive problems.